Fluorodeoxyglucose positron emission tomography/computed tomography imaging in pseudo Sister Mary Joseph's nodule - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Sister Mary Joseph's nodule (SMJN) refers to umbilical metastatic lesions and indicates widespread intra-abdominal malignancy. The most common primary sites are gastrointestinal and genital tract. Benign umbilical nodules are called pseudo-SMJN (PSMJN) and have been also reported in nonmalignant lesions such as endometriosis, fibroma, papillomas, myxoma, keloid, omphalith, nevi, foreign-body granulomas, and epidermoid cysts. We report a case with PSMJN as an extremely rare manifestation of intra-abdominal tuberculosis.
Keywords: Fluorodeoxyglucose positron emission tomography; computed tomography/peritoneal tuberculosis; pseudo Sister Mary's Joseph nodule; UMBILICAL METASTASIS